Hydrogen production by steam reforming of acetic acid and bio-oil using Ni/γ-Al2O3 catalysts - Yanmei, Li; Peng, Fu; Weiming, Yi; Xueyuan, Bai (International Journal of Agricultural and Biological Engineering, 2015)
Hydrogen production from steam reforming of bio-oil and acetic acid using Ni/γ-Al2O3 catalyst was studied in a laboratory-scale fixed bed reactor. This study selected different Ni loadings (16.8% and 30.5%) in Ni/γ-Al2O3 catalysts and reaction temperatures (500°C, 600°C and 700°C) as variables to optimize the hydrogen yield and selectivity of gases formed. Experiments were carried out in an isothermal manner. The catalysts were prepared on wet impregnation of a γ-Al2O3 which supported with two different Ni loadings. The principal gases generated were H2, CO, CO2 and CH4. The results from steam reforming of acetic acid showed that the yield and selectivity of hydrogen using the catalyst with 30.5% Ni were significantly higher than that with 16.8% Ni. The results showed that the most favorable temperature for hydrogen production was 600°C, and the steam reforming of bio-oil using Ni/γ-Al2O3 catalyst with 30.5% Ni showed that the yields and selectivity of H2 and CO2 increased with the temperature increasing while CH4 and CO selectivity decreased. These results showed that the most favorable temperature for hydrogen production from bio-oil using 30.5% Ni/γ-Al2O3 was 600°C, at which hydrogen yield was at its maximum of 65%. Keywords: hydrogen, bio-oil, Ni/γ-Al2O3 catalyst, steam reforming, acetic acid DOI: 10.3965/j.ijabe.20150806.1277 Citation: Li Y M, Fu P, Yi W M, Bai X Y. Hydrogen production by steam reforming of acetic acid and bio-oil using Ni/γ-Al2O3 catalysts. Int J Agric & Biol Eng, 2015; 8(6): 69－76.